PERANCANGAN SISTEM INFORMASI PEMESANAN JASA WEDDING ORGANIZER BERBASIS WEB - Rai Muslim; Deffy Susanti (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
The development of technology can affect many aspects, including the economy, politics, government, and many others. These influences have brought about many changes in lifestyle and the way people perceive things, particularly for those accustomed to and living within a technological environment. One of the most well-known information technologies in society is the internet, and websites are not only used to display information. The development of websites has greatly helped companies to support their activities, such as online ordering. In addition to the ordering process, data processing activities must also be computerized, starting from the processing of product data that can later be used to select pre-wedding photo packages according to customer preferences while maximizing the budget they have. This includes processing customer data from registration to ordering on the website. With the website, it is hoped that company information can spread widely and directly maximize performance. Generally, pre-wedding photo orders are still manually processed. Some common weaknesses found in companies that offer pre-wedding photo services include having a website, but the ordering process is still done manually. It would be better if the company processes orders directly through their website, making it more effective and efficient. In addition to the ordering process, data processing activities must also be computerized, starting from the processing of product data that can later be used to select pre-wedding photo packages according to customer preferences while maximizing their budget. This includes processing customer data from registration to ordering on the website. With a website, it is expected that company information can spread widely and directly maximize performance.